A case of TSC2‐PKD1 contiguous deletion syndrome: Clinical features and effective treatment for epilepsy. Issue 2 (25th January 2021) - Pan, Xiaoyu; Yang, Chengqing; Ma, Shaochun; Wang, Weihong; Liu, Peipei; Guo, Ya; Liu, Yedan; Song, Jie; Wu, Sifei; Yi, Liping; Wei, Wei; Chen, Zongbo
Abstract: Polycystic kidney disease with Tuberous sclerosis is a disease caused by the deletions of the TSC2‐PKD1 gene. The disease is rarely reported and the characterized manifestation is severe polycystic kidney growth. The diagnosis can be made by molecular analysis. We report the first case of PKDTS discovered in infancy in China with typical neurological and renal manifestations. The patient has infantile spasm, polycystic kidney, skin damage, hypertension, and hematuria after infection. After effective treatment of Rapamycin, the seizures were completely controlled. There was not been any renal function damage in the patient. At the same time, we review the related literature and further elaborate on the variety of clinical manifestations, treatment, and prognosis. Abstract : We report the first case of PKDTS discovered in infancy in China with typical neurological and renal manifestations. The treatment with rapamycin led to the effective treatment of seizures, normalization of EEG results, stabilization of renal cysts, and of renal function throughout the follow‐up period.